KARAKTERISTIK PRODUK BIOGAS DARI BERBAGAI JENIS LIMBAH SAYUR SAWI - Marcelino; Viktor; Anggorowati, Dwi Ana (Teknik Kimia ITN Malang, 2022)
Market waste in the form of vegetables is an organic material that is of concern considering that this waste is increasing every day and it is increasingly difficult to find a place for disposal and reduces the aesthetic beauty of the city (Giska, 2017). The type of mustard greens waste is an organic material that has the potential to be used as raw material for biogas. This study aims to determine the effect of different variations of mustard vegetable waste and cow dung on the biogas produced. The variation used was a mixture of cow manure with green mustard, chicory and meat mustard with successive ratios of 7:1, 5:1, 4:1. The mixture of ingredients is put into a simple airtight bioreactor and then carried out the fermentation process stage for 15 days. Then check the temperature and volume of gas produced every day and check the final pH. From the results of the study it was found that mustard greens obtained a higher gas volume on the 7th day, which was 690 mL compared to chicory and green mustard, which respectively produced a gas volume of 475 mL and 380 mL on the 8th day.